Novel neural pathways for metabolic effects of thyroid hormone - Fliers, Eric; Klieverik, Lars P.; Kalsbeek, Andries (Trends in endocrinology and metabolism, 2010)
The relation between thyrotoxicosis, the clinical syndrome resulting from exposure to excessive thyroid hormone concentrations, and the sympathetic nervous system remains enigmatic. Nevertheless, β-adrenergic blockers are widely used to manage severe thyrotoxicosis. Recent experiments show that the effects of thyrotoxicosis on hepatic glucose production and insulin sensitivity can be modulated by selective hepatic sympathetic and parasympathetic denervation. Indeed, thyroid hormone stimulates hepatic glucose production via a sympathetic pathway, a novel central pathway for thyroid hormone action. Rodent studies suggest that similar neural routes exist for thyroid hormone analogues (e.g. thyronamines). Further elucidation of central effects of thyroid hormone on autonomic outflow to metabolic organs, including the thyroid and brown adipose tissue, will add to our understanding of hyperthyroidism.